Study of Histopathological change in gills of Coptodon zillii as a bioindicator of pollution in Sarragy River In Abu Alkhasiib region - Samad, Khalid Abdul Samad; AL Ali, Ali A. A. (Iraqi Journal of Aquaculture, 2022)
In the present study the fish Coptodon zillii are collectedfrom Sarragy River in Abu Alkhasiib region through two season that the first is expansion from 7\2013 to 11\2013 and the second season is expansion from 12\2013 to 6\2014,and bringing it to the laboratory for dissection and ablation the gills for studied the histopathological change that appear on it, that included change of the form of some secondary lamellae, adherence in other secondary lamella ,cellular hyperplasia , hypertrophy , swelling in the epithelial layer of secondary lamellae, epithelial lifting ,and hyperplasia in cartilage skeletal of primary filaments.